Developing a differentiated learning approach using smartphone applications to reduce learning loss and enhance students’ motivation in English language learning - Siti Ngaisah; Salma Hira; Ekka Zahra Puspita Dewi; Edi Yulianto (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop an English language learning model based on a differentiated instruction approach utilizing smartphone applications to reduce learning loss and enhance students' learning motivation. The development model adopted follows the ADDIE framework by Borg & Gall, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The analysis stage was carried out through classroom observations, interviews, and questionnaires to identify learning needs, motivation levels, and students' access to technological resources. The design stage involved developing differentiated learning scenarios in terms of content, process, and product, integrated with smartphone applications such as YouTube, Pinterest, Wemoji and Quizzes for the